2021
DOI: 10.1371/journal.pone.0260406
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of photic phenomena in the presbyopia-correcting intraocular lens

Abstract: This was a prospective study to evaluate the feasibility of the photic phenomena test (PPT) for quantifying glare, halo, and starburst. We compared two presbyopia-correcting intraocular lenses (IOLs), the Symfony IOL and the PanOptix IOL, as well as the monofocal Clareon IOL in 111 IOL-implanted eyes of 111 patients who underwent the PPT 1 month postoperatively. The reproducibility of photic phenomena with the PPT was assessed in 39 multifocal IOL-implanted eyes of 20 patients and among the examiners. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Indeed, 74, 57 and 42% of patients reached a binocular VA higher than 20/25 at 40, 67 and 80 cm, respectively. This result was confirmed by the trend of the defocus curve and seems to be in accordance with the current literature ( 4–6 ). Authors would like to underline that these results appear to be in agreement with the available literature on Lucidis IOLs, as to our knowledge currently no study has ever reported the DCIVA, but only the UIVA (without specifying how many cm it was run) and none performed defocus curves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, 74, 57 and 42% of patients reached a binocular VA higher than 20/25 at 40, 67 and 80 cm, respectively. This result was confirmed by the trend of the defocus curve and seems to be in accordance with the current literature ( 4–6 ). Authors would like to underline that these results appear to be in agreement with the available literature on Lucidis IOLs, as to our knowledge currently no study has ever reported the DCIVA, but only the UIVA (without specifying how many cm it was run) and none performed defocus curves.…”
Section: Discussionsupporting
confidence: 93%
“…In the last decades premium multifocal intraocular lenses (MFIOL) have been designed to meet the patients' need for spectacle independence, however, these lenses frequently led to a bad quality of vision, especially at near and/or far distances. Other issues that have emerged through the years with these lenses consisted in the decrease of both contrast sensitivity and night vision, as well as in the frequent manifestation of visual phenomena such as halos, glare and starburst (especially with diffractive MFIOLs) (1)(2)(3)(4). Recently, the need to overcome these concerns has led to the development of new technologies able to generate a single focal point with an extended depth of focus (EDOF).…”
Section: Introductionmentioning
confidence: 99%
“…Multifocal IOLs have multiple optical zones with different refractive powers that allow for good VA at different distances, such as near, intermediate, and far. However, they may cause a reduction in contrast sensitivity and an increase in glare, which can affect the quality of vision 19 , 20 . In contrast, EDOF IOLs are designed to enhance visual range, especially at intermediate distances while maintaining a high level of continuous VA 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal IOLs have two, three, or four optical intensities which aim at obtaining a decent VA at selected distances [25]. Because such features lead to reduced contrast sensitivity, the frequency of glare is higher for multifocal IOLs than for monofocal IOLs [26,27]. EDOF IOLs, on the other hand, aim to extend the range of distant VA to intermediate distance and enable enhanced continuous VA [28].…”
Section: Discussionmentioning
confidence: 99%